Traços de Viagem: Experiências remotas, locais invulgares - Ramos, M. (2009)
A series of travels illustrated by the author in Tunisia, Spain, Zimbabwe, UK, Ethiopia and Portugal. One travels to experience falling outside the comfort of one's sedentary illusions; but because we also want to return, we must abandon the illusion of being part of worlds that are not and never will be ours. No traveller truly sees anything anew. We see what we've read and heard, read what he saw and felt. When writing or drawing imagined exotic realities, we pretend to forget that there is no other reality than shared fiction. The attraction of the journey is born of the urge to confront us for a moment with the abyss, where the illusions of our fragile daily reality threaten to stumble. And this moment is that of the click, which allows us to escape the illusions of a sedentary reality, and imprisons us in the illusion that we woke up from the nightmare of sedentariness. "More than literary accounts of his journeys, Manuel Joao Ramos offers the reader true ethnographic reports, that is, sudden dips into the complex realities of other countries, focusing on concrete stories of real people."